2021
DOI: 10.1155/2021/5561097
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Bond Properties between Normal Strength Concrete and Epoxy Resin Concrete

Abstract: It is necessary to pay attention to the bonding strength of the interface between precast normal strength concrete (NSC) and cast-in-place epoxy resin concrete (EMR) when using EMR as a repair or filling material or an overlay in bridges’ rehabilitation. However, the performances of epoxy concrete are different due to differential mix ratios; thus, the bonding properties between various epoxy resin concrete and cement concrete are not completely the same. This article investigated the interfacial bond properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…An epoxy resin binder is commonly used for concrete interface bonding nowadays [26]. In this test, the self-proportioning cement-based interface agents J A and J B were compared with the epoxy-based concrete interface agent J C , and the state without an interface agent was used as the reference group for comparison.…”
Section: Mixing Ratio and Stirring Processmentioning
confidence: 99%
“…An epoxy resin binder is commonly used for concrete interface bonding nowadays [26]. In this test, the self-proportioning cement-based interface agents J A and J B were compared with the epoxy-based concrete interface agent J C , and the state without an interface agent was used as the reference group for comparison.…”
Section: Mixing Ratio and Stirring Processmentioning
confidence: 99%
“…Previous studies have shown that the addition of a 0.5 mm thick bonding agent to a smooth concrete surface produces the same bond strength value as a rough surface without a bonding agent [11]. This is because the bonding agent can combine the pores between the mortar material and the concrete thereby reducing porosity [12].…”
Section: Introductionmentioning
confidence: 97%
“…Te interfacial bond strength consists of material bonding strength, mechanical bonding strength, and shear keyway shear strength, which depends on the surface roughness, adhesive, surface cleanliness, and water content. In practical engineering, interfacial cleanliness and wetness are the basic requirements, but the stability of interfacial adhesives is difcult to control and the efect varies [11,12]. Te control of surface roughness is the most critical.…”
Section: Introductionmentioning
confidence: 99%